Peningkatan Kapasitas Masyarakat Kopi di Desa Aik Berik, Kecamatan Batu Kliang Utara, Kabupaten Lombok Barat - Taslim Sjah; Halil Halil; I Ketut Budastra; I Gusti Lanang Parta Tanaya (Pascasarjana Universitas Mataram, 2020)
Coffee is one of the important plantation crops in West Lombok Regency, with one of the Robusta coffee production centers in Batu Kliang Utara district. This production is generally sold by growers in raw or unprocessed form, but some people do the processing individually or in groups. The coffee processing group has processed and marketed coffee with some success, characterized by their almost always depleted product. However, they stated that they still wanted to move forward and receive guidance or advice on different aspects of coffee from the aspects of production, processing, business development, marketing and the use of technology such as online marketing. This manufacturing problem is exacerbated by marketing and business management issues. In order to overcome these problems and at the same time improve the living conditions of the community, this service activity was carried out, namely transferring knowledge about increasing the capacity of the coffee community in Aik Berik Village, Batu Kliang Utara District, West Lombok Regency. The aim of this activity in general is to increase the income of community actors, especially coffee farmers and their families. The phases of activities to achieve these overall goals are carried out through specific objectives to improve technical marketing and management capabilities. Evaluation of activities shows positive results in the form of increased knowledge and enthusiasm for business due to the potential for increased benefits obtained through the application of the acquired knowledge and previous knowledge. Therefore, these types of activities must be redone in new locations and in new (business) activity fields. Awareness activities such as these must be carried out as they are necessary for the local community and the potential for natural and human resources to carry out these activities is quite high.